(untitled) (Research, Society and Development, 2025)
The objective of this study was to analyze the composition of the neonatal microbiome resulting from the mode of delivery and its pathophysiological repercussions. The systematic review followed the PRISMA protocol and utilized the PubMed database. The research included studies conducted in humans, published between 2019 and 2024, encompassing original articles, meta-analyses, and systematic reviews. This study excluded duplicate, incomplete, or thematically incongruent articles. The final selection included 421 results, and after screening, 5 met the eligibility criteria and aligned with the established objectives. The selected articles highlighted differences in the microbiota composition of infants born via vaginal delivery versus cesarean section, with these disparities being linked to physiological impacts on the immune, intestinal, and neurological axes. Among the key studies, 2 investigated possibilities for microbiota restoration, emphasizing breastfeeding and Vaginal Microbiota Transfer (VMT). Finally, the articles confirmed a relationship between the mode of delivery and neonatal microbiome modulation, reinforcing the need for further research to assess the long-term consequences of this association.